Dermasence refining gel modulates pathogenetic factors of rosacea in vitro. (27th March 2017) - Borelli, C; Becker, B; Thude, S; Fehrenbacher, B; Isermann, D
Summary: Background: Over the counter cosmetics sold for local treatment of slight to moderate rosacea often state the claim of actively modulating rosacea pathogenesis. Factors involved in the pathogenesis of this common yet complex skin disorder include kallikrein‐related peptidase 5 (KLK5), LL‐37, as well as protease‐activated receptor 2 (PAR2) and vascular endothelial growth factor (VEGF). Objective: The objective was to prove the modulating effect of the cosmetic skin care agent Dermasence Refining Gel (DRG) on factors involved in rosacea pathogenesis. Methods: We analyzed the effect of DRG on the expression of KLK5, LL‐37, PAR2, and VEGF in an in vitro skin model of human reconstituted epidermis. Results: The expression of CAMP (LL‐37 gene, fold change −4.19 [±0.11]), VEGFA (fold change −2.55 [±0.12]) and PAR2 (−1.33 [±0.12]) was reduced, KLK5 expression increased (fold change 2.06 (±0.08)) after 18 h of treatment with DRG in comparison to treatment with the matrix gel only. The reduction in CAMP expression was significant ( P <.01). The protein expression of all four inflammatory markers was markedly reduced after 18 hours of DRG treatment in comparison to baseline (0 hour), by measure of fluorescence intensity. Conclusion: We show evidence explaining the anti‐inflammatory effect of Dermasence Refining Gel in rosacea pathogenesis in vitro. The adjunctive use of DRG in mild to moderate rosacea as a topical cosmetic seems medically reasonable.